(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Agriculture has been critical in the development of human civilization. Agriculture has been the most popular activity among people for decades. Agriculture is the most commonly employed sector, employing a huge number of people. Agriculture has a number of issues, including soil erosion, inadequate storage facilities, and irrigation. Growing plants and rearing animals is the science and practice of agriculture. Agriculture encompasses a wide range of methods and activities, including pastoral farming, shifting agriculture, mixed farming, nomadic agriculture, commercial agriculture, intense and extended farming, and many more. The introduction of agriculture, kinds of agriculture, the importance of agriculture in development, and new agricultural technology in contemporary farming such as indoor vertical farming, farm automation, and blockchain are all discussed in this study. This research is beneficial to anyone who are interested in agriculture. New technologies will be introduced to the agricultural sector in the future, allowing for the production of higher-quality goods while also resolving the issues that come with them.